THE EFFECTIVENESS OF NATIVE ADVERTISING IN DIGITAL MEDIA (International Journal of Food and Nutritional Sciences, 2022)
This study examines the effectiveness of native advertising in digital media, a rapidly growing segment of online marketing. Native advertising refers to promotional content that blends seamlessly into the surrounding editorial content, designed to match the platform’s form and function. As consumers become increasingly ad-averse and utilize ad blockers, traditional advertising methods often fail to capture attention. Native advertising addresses this challenge by providing a less intrusive alternative that engages users through relevant, informative, and entertaining content. The effectiveness of native advertising is evident in its ability to enhance user engagement, brand perception, and trust. Research indicates that consumers are more likely to interact with native ads than traditional display ads, resulting in higher click-through rates and increased time spent on content. By delivering valuable information, brands can position themselves as thought leaders, fostering positive associations and enhancing credibility. Moreover, the shareable nature of native content, particularly on social media, amplifies brand visibility and reach.